MANAJEMEN STRATEGIS LUMAJANG PRESISI UNTUK MEWUJUDKAN SMART POLICE DI KEPOLISIAN RESOR (POLRES) LUMAJANG - Yesicha Harialifa Pramudita; Meirinawati Meirinawati (Universitas Negeri Surabaya, 2022)
The emergence of E-Government is considered to be the answer to public service problems that are still considered old and complicated by the community. Service is a very important basic thing because it determines the public's perception or assessment of the performance of an agency. Therefore, with this trend, many agencies are competing in improving their service performance by creating E-Government. As is the case with the Lumajang Police, which also seeks to implement Smart Governance with the Smart Police concept, which is marked by the existence of Lumajang Precision in responding to public service problems whose performance has not been maximized. The purpose of this study is to describe the strategic management concept of the Lumajang Presisi application from planning to performance evaluation. This study uses a descriptive qualitative approach by determining informants using snowball sampling and using strategic management theory, namely the two important things in strategic management proposed by Niswah and Meirinawati. Data collection techniques using interview techniques, observation, and literature study. While the data analysis technique uses four stages, namely data collection, data reduction or data grouping, data presentation, then the last stage is drawing conclusions. Based on the theory and data analysis techniques that have been used, the results obtained are the elements in two important things in the Menstra of the Lumajang Presisi application that are carried out well and provide benefits to the community. Keywords: Strategic Management, Smart Governance, Smart Police.